ANT FAUNA ASSOCIATED WITH TROPICAL PASTURES AND ITS ROLE AS PREDATORS OF EGGS AND NYMPHS OF THE SPITTLEBUGS Aeneolamia spp. - MEDINA, CLAUDIA ALEJANDRA; LAPOINTE, STEPHEN L.; CHACÓN, PATRICIA (Revista Colombiana de Entomología, 1993)
Currently, there is an increasing utilization of tropical savanna areas with established pastures of introduced grasses of the genus Brachiaria. Despite their excellent adaptation to acid and infertile soils, Brachiaria grasses are highly susceptible to the spittlebugs Aeneblamia spp. Here we report on the results of a study about ants associated with introduced and native pastures and their role as predators of spittlebugs. We found a group of generalist predatory ants that consume spittlebug eggs artificially placed in the field. Ants of the genera Solenopsis, Wasmannia, and Pheidole were observed most persistently preying upon spittlebug egg masses and first-instar nymphs. Other species such as Paratrechina sp., Ectatomma ruidum y Camponotus sp.1 were also observed consuming spittlebug eggs. To study the diversity, species composition, and abundance of ants associated with introduced and native pastures, we sampled plots by placing baits at different distances. Baits placed every 5 m captured up to 83% of the species collected with more time-consuming methods such as manual collection and nest digging. A total of 41 ant species associated with all pastures were collected with all methods. Among the introduced pastures, B. decumbens cv. Basilisk had the greatest number of associated ants (18 species). The patterns of the spatial distribution of nests of Brachymyrmex sp., E. ruidum and Camponotus sp.1 in a plot before and alter soil preparation for sowing Brachiara hybrids were also documented. After soil preparation, Camponotus sp. 1 nests disappeared but nests of one Solenopsis species were found in the plot.